Tanggung Jawab Ayah Sebagai Pembina Rohani dalam Meningkatkan Mutu Spritualitas Anak Usia 0-17 Tahun - Amelia Kartika Wabang (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The failure of parents to teach responsibility to children will cause various bad effects for children both now and in the future. Responsibilities are important in children's lives because they are correlated with children's emotional intelligence, social relationships, have a good impact on educational aspects, and contribute to children's success in the future. Because of the closeness of the relationship and the bonds they have, parents are the most appropriate person to teach responsibility to children. This research article aims to highlight what role Christian parents can play in contributing to the maximum in teaching their children about responsibility. By using the description method and getting support from literature review, it is hoped that it can provide a strong and in-depth picture related to the discussion of Bible stories about responsibility, the importance of responsibility for children, and the contribution of parents in teaching responsibility to children. The results of this study found that parents can contribute maximally in teaching responsibility to children when they begin to introduce responsibility as early as possible, make responsibility a habit of behavior, become role models, and be sensitive when teaching children. Through living these five things in real life by parents, parents will contribute maximally to the growth of children's responsibilities.